Universities' foundation and regional development - Viktor Slavtchev; Florian Noseleit (European Regional Science Association (ERSA), 2010)
Universities are assumed to be agents of change. The underlying assumption is that they create new technological knowledge and opportunities that may cause some industries to decline and to disappear and other industries to emerge and to growth. In fact, previous research provides some evidence that the spatial and temporal emergence and evolution of industries, particularly knowledge intensive ones, is related to public research. Against this background, this paper analyzes the impact of the foundation of universities on structural change in the region. In particular, we use information about the foundation of universities in West German regions over the period from 1975 to 2002. Structural change in the region is measured by the Modified Lilien Index (MLI) based on employment shares in 19 NACE 2-digit private industries. The MLI index is calculated for every West German region and measures the change in the sectoral composition of employment in the region between two points in time. The proposition that foundation of a university foster structural change in the region is empirically tested by applying difference-in-difference approach. This underlying idea is to compare the growth difference in the MLI of two groups of regions: such that have been exposed to a treatment (foundation of a university), and such that have been not. The average treatment effect is then calculated as the growth difference of the structural change index between the two groups. Moreover, regarding the impact of university's foundation, two additional effects are considered. First, the impact of university's foundation may occur with a certain time lag since some time is required for academic knowledge to disseminate to the private economy. Possible reasons for such time lags may be that some time is required for students to graduate, and for university-industry collaborations and academic entrepreneurship to take place. Second, the impact of university's foundation may be not one-shot but rather permanent. Moreover, it seems reasonable to assume that universities are rather small at the time of foundation and growth over time to reach an optimal size. The results of the empirical analysis provide evidence that universities may act as agents of change.
Keywords: 330; structural change; regional development; universities